How to Have (Critical) Method in a Pandemic: Outlining a Culture-Centered Approach to Health Discourse Analysis - Sastry, Shaunak; Basu, Ambar (Frontiers in Communication, 2020)
In this elucidative essay, we offer a broad outline of the culture-centered approach to health discourse analysis the relevance of critical health communication amid the global COVID-19 pandemic. While there is a proliferation of methods and approaches to health discourse analysis, we outline one broad approach, based on the theoretical tenets and political commitments of CCA. In particular, we emphasize a) the heuristic value of the CCA's primary and theoretical components –the matrix of culture, structure, and agency, and b) the importance of exploring discursive erasure as two central principles that guide analysis within this framework. Given the range and scale of existing and likely future transformations in social, political, and cultural understandings of health in the wake of the global COVID-19 pandemic, we offer, through this "how-to" essay, a rationale for the continued relevance of critical health communication.